Effects of load shifting on water quality in a large potable water network - Jansen van Rensburg, Francois Gysbert (My University, 2015)
Mathematical analyses indicated that significant possibilities exist for load shifting projects on a Large Potable Water Utility (LPWU) in South Africa. A primary concern remained, i.e. whether the load variation would have an effect on the water quality. Extensive simulation and testing were initiated in order to prove that the load shift will not affect the water quality. In South Africa, the highest standard for drinking water is the Blue Drop award. The LPWU has received this award multiple times and strives to maintain it. An investigation was launched to determine if this load shifting project would have an effect on the quality standards to which the utility holds (SANS 241 (2011)). The LPWU has over 3000 km of pipelines to supply potable water to the industrial heartland of the country as well as millions of domestic users. The LPWU network is the longest pumping network in the world and is still expanding. The investigation included a simulation of a pumping simulation package to determine how the system would react to the changes. In this simulation, the load reduction in terms of Mega litre per day (Ml/day) was established. Results were compared to the normal operating parameters of the Water Treatment Works (WTW). The mathematical analysis in this investigation concluded that an evening peak load shift of 24.5 MW is achievable. This dissertation will emphasise the necessity of a detailed investigation. The investigations and simulation will determine that the volume of water is well within the operating parameters of the WTW. Studies were done on each area of the plant. In-depth conversations with WTW personnel revealed that the reduction of the volume of water in question will not have an effect on the water quality. Further, it was established that it would be possible to use the sumps of the water treatment works to achieve the desired load shift. By using the sumps of the WTW, a load shift can be done without stopping any process in the WTW with the exception of disinfection at the Booster Pump Stations (BPS), where the balancing reservoirs were used as buffer capacity. The investigation shifted to establish whether stagnant water and a change in dosage would have an effect on the water quality in regard to the reduction and recovery load. As expected, the water never became stagnant at any moment due to the fact that only a small portion of the load was reduced. The water quality and dosage report of the water utility was used and compared to normal operations. The planned load shift had no effect on any aspects of the water quality. The project is feasible and will reach the set targets without affecting the water quality.
MIng (Mechanical Engineering), North-West University, Potchefstroom Campus, 2015
Keywords: Water quality; Load shifting; Potable water network; Water distribution network; Blue Drop; Water treatment